Enhancing Students’ Collaborative Skills through Padlet-Assisted Open-Ended Problem-Based Learning in Sociology Classrooms - Widya Trisna; Erianjoni; Syafri Anwar; Eka Asih Febriani (JPI: Jurnal Pustaka Indonesia, 2026)
This study addressed the limited collaboration skills observed among Grade XI students in Sociology learning at SMAN 1 Batipuh, as reflected in passive participation, unequal task distribution, limited interpersonal communication, and insufficient responsibility during group activities. The study aimed to examine how Problem-Based Learning (PBL), integrated with Open-Ended Collaboration and supported by Padlet, facilitated the progressive improvement of students’ collaboration skills. A Classroom Action Research design was employed through two cycles, with each cycle comprising planning, action, observation, and reflection stages. Data were collected using structured classroom observations, collaboration skill assessments, semi-structured interviews, field notes, documentation, and students’ digital interaction records on Padlet. The collaboration assessment was adapted from Crebert’s teamwork framework and focused on group collaboration, contribution toward shared goals, responsibility and interdependence, and interpersonal communication. Qualitative data were analysed through data reduction, data display, thematic interpretation, and conclusion drawing, while quantitative data were examined using mean scores and percentage-based performance categories. The findings indicated progressive improvements in students’ active participation, equitable contribution to group tasks, responsibility for assigned roles, confidence in expressing ideas, peer feedback, and collaborative problem-solving across the research cycles. Padlet supported continuous interaction, documentation, idea sharing, and reflective feedback throughout the learning process. The findings suggest that the pedagogical integration of authentic social problems, multiple solution pathways, structured collaboration, teacher scaffolding, and digital mediation can create a more participatory and accountable Sociology learning environment. This integrated instructional approach therefore offers a contextually relevant strategy for strengthening collaboration skills as an essential component of twenty-first-century education.